THE IMPORTANCE OF EDUCATIONAL AND EDUCATIONAL INTERACTIVE GAMES IN EARLY GRADES - Daminova Gulnora Abdusamatovna (Web of Journals Publishing, 2024)
In the main content of the article, interactive methods in primary grades, their types, the role of modern technologies in the educational process, methods of application in primary grades, modern pedagogy of primary grade teachers of general secondary schools opportunities to use technologies.
Keywords: pedagogical technologies, interactive methods, form, method, tools, brainstorming, networks, cinquain, zigzag, work in small groups, debate, fsmu, rounded snow, ict, modern methods, modern form of teaching, internet, electronic mail.